PERBEDAAN KARAKTER TIGA JENIS BENTONIT DITINJAU DARI TIGA MACAM CARA ANALISIS - Koestiari, Toeti (Sains & Matematika, 2013)
The objective of this research was to determine differences in the physico-chemical character of the bentonite-Sigma (BS) compared with Al pillared bentonite (B-Al/400° C), and technical bentonite (BT) so we can know the nature of the surface. This experimental research laboratory using three instruments, namely Buck Scientific IR Spectrophotometer - 500, Gas Sorption Analyzer Quantachrome NovaWin2, and Scanning Electron Microscope (SEM-EDX).The result of this research showed the differences in physico-chemical character of BS, B-Al/400° C and BT in terms of: (1) The position of the main functional groups using IR Spectrophotometer instrument; (2) The surface areas of B-S, B-Al/400° C, and B-T are 24.78 m2/g; 217.021 m2/g; and 51.935 m2/g, while total pore volume for the pore radii smaller than 1001.9 Å? (B-S) and smaller than 1273.1 Å? (B-Al/400 oC) and less than 1013.9 A? (B-T) using Gas Sorption Analyzer. (3) Using SEM-EDX indicated that the percent mass compounds of B-S are Al2O3: 19.78%, and SiO2: 80.22%; the percent mass compounds of B-Al/400° C are Al2O3: 30.43%, and SiO2: 69.57%. the percent mass compounds of B-Tare Na2O: 2.64%; Al2O3: 20.75%, SiO2: 57.55%, FeO: 13.73%.